PENYUSUNAN INSTRUMEN KEPRIBADIAN GURU - Isnaeni, Maulina; Wahdani, Mahmida Farah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Developing personality instruments to evaluate a teacher's characteristics and psychological aspects has become a major focus in educational research. This study aims to develop a valid and reliable instrument to measure personality dimensions relevant to the educational context. The research method used is library research, which involves reviewing literature to identify personality dimensions suited to teacher performance and developing questionnaire items based on a theoretical framework. The process of drafting teacher personality assessments begins with an instrument blueprint (table of specifications) aligned with predetermined competencies. Once the blueprint is established, it is developed into specific questions to create an effective assessment. Regular teacher personality assessments are expected to support the ongoing development of a teacher's personality.